Propofol/Etomidate Induced and Isoflurane Maintained Anaesthesia in Dogs - Kantia, Rajwanti G.; Jhala, Shivrajsinh K.; Suthar, Deepakkumar N.; Dabas, Vijander Singh (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Twenty-four clinical cases of dogs presented for surgical interventions requiring general anaesthesia were randomly divided into four groups (n=6) irrespective of age, breed, sex, body weight and surgical procedure. The animals of group I and II were first premedicated with atropine sulphate @ 0.02 mg/kg BW and butorphanol @ 0.2 mg/kg BW intramuscularly; whereas, atropine sulphate @ 0.02 mg/kg BW and buprenorphine @ 0.02 mg/kg BW was administered intramuscularly in animals of group III and IV, followed by diazepam @ 0.5 mg/kg BW intravenously in all the dogs. Induction of anaesthesia was achieved by intravenous administration of 1% propofol in group I and III and 0.2 % etomidate in group II and IV till effect. Dose sparing effect of pre-anaesthetic drugs, anaesthetic duration, viz., duration of surgery, duration of maintenance of anaesthesia, total duration of anaesthesia, recovery time and quality parameters, viz., quality of sedation, induction, maintenance anaesthesia and recovery were recorded. There was significant reduction in the induction dose of etomidate as well as recovery time as compared to propofol with both the pre-anaesthetic agents. The induction dose of propofol was also significantly reduced particularly with butorphanol than with buprenorphine. Duration of surgery, duration of maintenance of anaesthesia and total duration of anaesthesia were apparently lower in group IV than other three groups, but the duration of surgery only differed significantly due to variety of surgical procedures. Quality of sedation, induction, maintenance anaesthesia and recovery were found good to excellent in all the groups.
Keywords: Anaesthesia; Dog; Etomidate; Isoflurane; Propofol